The nursery child and fairy tales - Nyitrai, Ágnes (Autonomy and Responsibility Journal of Educational Sciences, 2022)
In recent years, the results of research on early childhood development have been even more nuanced than in previous decades, evidence that storytelling in the life of a young child significantly influences later development. These findings have brought new emphases enrich methodological approaches. One of the possible methodological developments basis for a competence-based approach, which would apply to the on the development of competences, and on the impact of the adult (parent and teacher) who tells the story the development of the storytelling competences of the storytelling educator.